2010
DOI: 10.1002/marc.201000556
|View full text |Cite
|
Sign up to set email alerts
|

Highly Extensible Bio‐Nanocomposite Fibers

Abstract: Here, we show that a poly(ethylene oxide) polymer can be physically cross-linked with silicate nanoparticles (Laponite) to yield highly extensible, bio-nanocomposite fibers that, upon pulling, stretch to extreme lengths and crystallize polymer chains. We find that both, nanometer structures and mechanical properties of the fibers respond to mechanical deformation by exhibiting strain-induced crystallization and high elongation. We explore the structural characteristics using X-ray scattering and the mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…Contact guidance plays a significant role in numerous biological processes such as cell migration (Clark et al , 1990). In addition, cytoskeletal components including actin filaments as well as focal adhesion complexes are organized along with the direction of the features (Nikkhah et al , 2012a; Gaharwar et al , 2011). Therefore, similar process is expected to take place when endothelial cells are cultured on the PGS-PCL scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…Contact guidance plays a significant role in numerous biological processes such as cell migration (Clark et al , 1990). In addition, cytoskeletal components including actin filaments as well as focal adhesion complexes are organized along with the direction of the features (Nikkhah et al , 2012a; Gaharwar et al , 2011). Therefore, similar process is expected to take place when endothelial cells are cultured on the PGS-PCL scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that cells elongate along the fiber axis and cellular morphology play an important role in cellular behavior. [34, 69] The interaction between hMSCs and electrospun scaffolds was evaluated by monitoring hMSCs adhesion and proliferation on scaffolds. All the scaffolds allowed cellular adhesion and proliferations, as well as the organization of the cell body on the fibers.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 This is due to anisotropic and plate-like, high aspect-ratio morphology of nanoclay, which results in high surface interactions between the polymers and nanoparticles. Nanoclays are widely used to reinforce thermoplastic polymers in order to obtain hybrid composites with hierarchical structure, 23,24 elastomeric properties, 25 ultrastrong and stiff films, 26,27 super gas-barrier membrane, 28 superoleophobicity surfaces, 29 flame-retardant structures, 30 and self-healing hydrogels. 31 A recent study has shown that nanoclay (synthetic silicates nanoplatelets) can induce osteogenic differentiation in hMSCs without using any growth factors.…”
mentioning
confidence: 99%